If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + -1x) = 4(2 + 1) (5 * 3 + -1x * 3) = 4(2 + 1) (15 + -3x) = 4(2 + 1) Combine like terms: 2 + 1 = 3 15 + -3x = 4(3) Multiply 4 * 3 15 + -3x = 12 Solving 15 + -3x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -3x = 12 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = 12 + -15 -3x = 12 + -15 Combine like terms: 12 + -15 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| -84=-7(r+6) | | 5(x+4)-6=5x+2 | | psquared-10=-6 | | 5(n-1/10)1/2 | | 3/10+3/20= | | 15*5/6= | | 2(x+6)=x+5 | | 3y-2(3)=4 | | -6(8r+8)=32-8r | | 12(2+2n)=-4(-12-1) | | 2(3m-4)-2=2(1-3m)-12 | | 3y-2(2)=4 | | x+42-x=180 | | -11a+6a=-12(a-6)-9(-a+8) | | 1=-(-w-6) | | 2x+3=8x-15 | | 2+(1-7x)-2=-112 | | 28=x/6+7 | | 15-x=6x-16 | | 7y+3-9y-8= | | 14-2x=-7x-6 | | -2(5.25+6.2x)=4(-3.1m+2.68) | | X^2+8x+51=0 | | 0.2x+0.1=x-2 | | 0=x*2-x+1 | | b-(-7.2)=-8.3 | | 25.56/3.7 | | 3(t-6)=12 | | 6a+9=-4+29 | | -45=a+14 | | 5y/2y+3=5 | | x-42-x=180 |